(untitled) (European Journal of Marketing and Economics, 2020)
Social entrepreneurship as an event appeared in XIX century. However, the emergence, development, forms of origin, scale of activity and speed of dissemination of social entrepreneurship are uneven across countries due to objective institutional factors. Based on the analysis of the emergence and development of social entrepreneurship worldwide, we can say that social entrepreneurship is a global event, which, on the one hand, extends to all regions of the world, on the other hand, has its national forms and characteristics depending on the degree of development of institutions, traditions and cultures in any one country. In generalizing the key trends in the development of social entrepreneurship worldwide, we can infer that the temporal and geographical frameworks for the spread of social entrepreneurship are driven by objective preconditions. Historical, political and socio-economic factors have influenced the period of formation of social entrepreneurial firms, organizational-legal forms and the intensity of the spread of social entrepreneurship in different regions of the world. The article discusses the regional features of social entrepreneurship development not only in countries where it has an established tradition, but also in countries where social entrepreneurship is starting to emerge. The main objective of the presented analysis is, on the one hand, to show the global scale of this event worldwide, and on the other, to reveal its national features.